2014
DOI: 10.3109/10717544.2014.991432
|View full text |Cite
|
Sign up to set email alerts
|

Development of lipid nanoparticles for a histone deacetylases inhibitor as a promising anticancer therapeutic

Abstract: Background: Vorinostat (VRS), a histone deacetylases inhibitor, has significant cytotoxic potential in a large number of human cancer cell lines. Objective: To clarify its promising anticancer potential and to improve its drawback related to physical properties and in vivo performance of VRS. Methods: VRS was successfully incorporated into nanostructured lipid carriers (NLCs) by the hot microemulsion method using sonication following a homogenization technique. Results: After the optimization process, VRS-load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…As VRS and DTX are both hydrophobic drugs, they can be carried on a lipophilic, biocompatible vehicle with a high loading capacity to amplify their activity [4,38,39] . In the past few decades, lipid carriers have proven an attractive option through the incorporation of hydrophobic agents into the lip ophilic matrix as an effective delivery system into the body [40,41] .…”
Section: Resultsmentioning
confidence: 99%
“…As VRS and DTX are both hydrophobic drugs, they can be carried on a lipophilic, biocompatible vehicle with a high loading capacity to amplify their activity [4,38,39] . In the past few decades, lipid carriers have proven an attractive option through the incorporation of hydrophobic agents into the lip ophilic matrix as an effective delivery system into the body [40,41] .…”
Section: Resultsmentioning
confidence: 99%
“…Better strategies to enhance the bioavailability of vorinostat are therefore needed. While previous studies have investigated the use of polymeric and lipidic nanoparticles to deliver vorinostat for tumour therapy [38,47,48,49,50], the majority of these studies focused on the intracellular delivery of vorinostat in cancer cells. Recently, Kim et al, encapsulated vorinostat within solid lipid and liquid lipid, and showed marked improvement in oral bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kim et al, encapsulated vorinostat within solid lipid and liquid lipid, and showed marked improvement in oral bioavailability. However, their formulation suffered from low encapsulation capacity (~2–3% loading), and the effect of encapsulation on solubility, permeability and anti-cancer activity was not studied [38,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An improvement of the anti-tumor effect was observed when the vectored HDACi was combined with chemo–radiotherapy and compared to the free HDACi [15]. When loaded in solid lipid nanoparticles or nanostructured lipid carriers, vorinostat is more cytotoxic on breast cancer and lung cancer cell lines than the free drug [12,16]. Cholesteryl butyrate solid lipid has shown a better activity than the free butyrate on breast and promyelocytic leukemia cancer cell lines [17].…”
Section: Concepts For Delivery Of Epigenetic Modulatorsmentioning
confidence: 99%